Constructions of platform edges of urban transport in complex cases - Gisterek, Igor (Przegląd Komunikacyjny)
The work is a continuation of the first part of 2017, where the contribution to the development of the optimal solution of horizontal and vertical distance between the platform edge and the tram threshold in Wrocław was presented. The general argumentation for the development of collective rail transport in cities was described, and the basic features of an attractive public transport system were also discussed. The historical and ongoing works were collected focusing on the location of the wagon floor in relation to the platform, taking into account selected foreign regulations. Presented are solutions that can be used in Wrocław conditions, describing more complex cases, complementing the first part: the possibility of expanding the carbody above the platform edge, tram and bus platforms or stops for tramtrains. The principles of creating an example algorithm for the proper selection of the edge structure of the platform have been proposed. The paper concludes with a summary and conclusions for both parts of the work. Keywords: Urban transport; Tramway; Platform; Tramway and bus stop